Quantifying Digital Competence (DigCompEdu) of agriculture teachers in Technical and Vocational Education and Training (TVET) Institutions - Yusof, Ma Sharipah; Mohd Puad, Mohd Hazwan (Faculty of Educational Studies Universiti Putra Malaysia (UPM), 2024)
The purpose of this study is to identify the level of digital competence among agriculture teachers in vocational colleges by using the Digital Competence Framework for Educators (DigCompEdu). The differences in the level of digital competence were analyzed according to demographic variables. A survey was conducted with 177 agricultural teachers from six vocational colleges in Malaysia using a proportionate stratified sampling method. This quantitative study was conducted to determine differences between 6 areas in digital competence with age, gender, and teaching experiences. The findings revealed that most agriculture teachers in vocational colleges fell into category B1, known as Integrators, and possessed moderate levels in all areas of digital competence. The data showed that gender did not significantly affect any of the digital competence areas examined. There was a significant difference in digital competence among agriculture teachers based on age and teaching experience in several areas. For Professional Engagement, younger teachers exhibited higher engagement levels, while for Digital Resources, teachers with 6–14 years of experience showed a significantly greater usage than those with 0–5 years. These findings underscore the importance of enhancing teachers' digital competence and understanding the various factors influencing it to meet future professional quality expectations and better prepare students for the digital world.